Oxidative stress in brain tissue of gerbils experimentally infected with neospora caninum - Tonin A.A. (2014)
Neospora caninum infection is generally latent and asymptomatic, and it results in the formation of dormant encysted bradyzoites that remain in the brain and other tissues of infected animals for life, causing major economic and pathological problems. The aim of this study was to assess the relation between infection by N. caninum and its damage to brain tissue through the evaluation of biomarkers of oxidative stress during the acute and chronic phases of the disease. Sixteen gerbil (Meriones unguiculatus) were divided into 3 groups: Group A (n = 6) was composed of healthy animals, while group B (n = 5) was infected with 0.1 ml containing 2.5 × 106 tachyzoites of N. caninum in order to achieve the acute phase, and, finally, group C (n = 5) was infected with a lower dose (0.1 ml containing 5 × 104) of N. caninum tachyzoites in order to produce the chronic phase of the disease. All evaluations were performed on brain tissue on days 7 and 30 postinfection (PI), with assessment of the levels of several biomarkers of oxidative stress, including nitrate/nitrite (NOx), lipid peroxidation (TBARS), protein oxidation (AOPP), and activity of glutathione reductase (GR). Brain levels of TBARS and AOPP statistically differed (P < 0.05) among the 3 groups when compared to the control group, since both biomarkers showed reduced levels on day 7 PI, and increased levels on day 30 PI. Brain activity of GR increased significantly in animals from group C when compared to groups A and B. On day 7 PI, histological lesions and parasites in the brain were not observed, whereas in the chronic phase group, the infected gerbils (day 30 PI) showed areas of inflammatory infiltrate, accompanied by the presence of the parasite in the brain. These results suggest that the oxidative stress occurs at both time points, but the patterns of the biomarkers are different. © American Society of Parasitologists 2014.